Response of Two Different Strains of Commercial Broilers to Different Dietary Amino Acid Allowance - B Indarsih (Media Peternakan, 2009)
The response of Cobb and Ingham strain commercial broilers to a range of dietary amino acids in a factorial experiment (2 strains x 2 sexes x 3 dietary treatments) with 3 replicates was evaluated. A total of 180 birds was sexed and weighed at one-day-old and randomly distributed to 36 brooders. Summit (246 g CP and 16.8 g lysine/kg) and dilution (120 g CP and 6.0 g lysine/kg) diets were prepared in isocaloric at 3100 kcal ME/kg. The estimated dietary level of crude protein for all birds at day-old was 240 g/kg and at 42 days were 120, 140 or 160 g/kg for females or 140, 160 or 180 g/kg for males. Body composition was measured at 42 days. Results revealed that strain Cobb males and females had a higher daily intake than Ingham, but Cobb females were less efficient in converting feed to weight gain than that of Ingham. The quantitative differences did not exist between genotypes, crude protein and lysine. Daily gain and feed utilization efficiency in both sexes were highest in group receiving the high protein diet. Lysine requirement was 14.58 g lysine /kg diet and 12.96 g/kg higher than NRC recommendation (1.05 % or 10.5 g/kg) for maximum breast meat and lowest abdominal fat. Key words: lysine, summit, dilution, breast meat, abdominal fat